Environment, Resources and Sustainable Tourism Goa as a Case Study - Dessai, Ashoka G. (Singapore : Springer Nature Singapore : Imprint: Springer, 2023)
This book suggests sustainable economy from the viewpoint of tourism fostering low carbon footprint. Focussed on conserving heritage, culture and endemic biota of a crucial biodiversity hotspot of the world, the book discusses the impact of a large population, fast-paced development and excessive consumption of earth resources by tourism in a developing economy. The book (i) assesses the impact of overexploitation of earth resources on environmental components such as air, water, land and people, (ii) examines the sustainability of tourism on the physical, economic and socio-cultural environment including human lifestyles, (iii) presents the potential of tourism in promoting sustainable development, poverty alleviation and conservation of nature and (iv) formulates recommendations for tourism, fostering sustainable development in Goa, India. The book offers students, researchers, academics and professionals a comprehensive discourse integrating geological and societal perspectives on core issues. It generates critical thinking on the complex issue of sustainable tourism by providing in-depth perspective on peoples of different hues and their role in safeguarding the future of this unique region. .
Introduction -- Mineral Resources -- Mining Industry -- Water Resources -- Environmental Assessment -- Waste Management -- Sustainable Tourism.
Keywords: Human ecology -- Study and teaching; Power resources; Tourism; Sustainability; Water; Hydrology; Refuse and refuse disposal; Environmental Studies; Natural Resource and Energy Economics; Tourism Economics; Sustainability; Water; Waste Management/Waste Technology